Compositional screening of Zr-Nb-Mo alloys with CALPHAD-type model for promising bio-medical implants. (March 2017) - Liang, J.S.; Liu, L.B.; Xu, G.L.; Wang, X.; Zhang, L.G.; Shi, X.; Tao, X.M.
Abstract: The increasing demands for biological hard tissue replacements (HTR) press on the development of biomedical implant materials with good biological and mechanical compatibility. Three criteria of screening promising alloy compositions for bio-medical application were proposed: (1). High thermodynamic stability of biological compatible phase to avoid β _bcc→ α _hcp and β _bcc→ αʹ _hexagonal transformations. (2). Positive tetragonal shear elastic constant C′ and shear modulus to avoid the acoustic lattice softening induced structural transformation. (3). Appropriate Young's modulus of β _type alloy in or close to 10–30 GPa to avoid the "stress-shielding effect". To validate the proposed criteria, the initiatives of computational screening for candidate compositions of Zr-Nb-Mo alloys were implemented by CALPHAD based modeling. With the thermodynamic calculation, not only the plot of T 0 contour was employed to indicate the boundaries of non-classical decomposition of β _bcc phase and martensitic transformation, but also the composition range in which the alloys exhibit relative low critical driving force to trigger nucleation and growth of α _hcp was determined. The Young's modulus at body temperature and the contour of the vanishing tetragonal shear elastic constant were predicted within the entire composition range. By superimposing the composition ranges which individually satisfy the criteria, the "candidate composition" were determined as Zr-(18−24)Nb-(0−3)Mo (atom%). They are in good agreement with the composition in the experimentally fabricated biomedical alloys, thus further exemplify the reliability of the criteria. The proposed criteria together with the CALPHAD based computational methodology as a whole open up a new way to develop the potential bio-medical materials in the framework of Materials Genomes.